Minat Mahasiswa Pendidikan Teknik Bangunan Terhadap Jasa Konstruksi Teknik Sipil - Renata Shinta G Simamora; Amos Neolaka; Dadang Suyadi (Jurnal Pensil : Pendidikan Teknik Sipil, 2013)
The objective of this study to find out the percentage of Interest of Educational civil engineering with engineering construction services. The study was conducted in May-July 2012. The methods used to determine the percentage of student interest in construction services is a descriptive study with survey methods or qualitative approach method then it doesn't test the hypothesis. This research was conducted on student of civil engineering State University of Jakarta amounted 360 undergraduate student Population enrolled in semester 096 (2011/2012), with a total sample of 50 students. Determination of samples used Random Sampling with Statified picked up 14% of the total population. Instruments in this research is non-test instrument. Testing instruments reabilitas questionnaire results obtained by 0.91 meaning belongs to the category of high reability. The results of Interest of Educational civil engineering with engineering construction services based on interest indicator from the desire of students is 32.68% Medium Interests category, an interest indicator of kinds activities is a 63.78% interest in the medium category, an interest indocator effort was 34.84% interest in the medium category, and results obtained on the terms of the average percentage of students was 132.8% interest in the category of Medium Interests.